Photosystem I photoinhibition in abnormal CO2 concentration - Käpylä, Ville (My University, 2025)
Photosynthesis is responsible for fixation of carbon into organic form, and thus it is essential for both the ecosystems in Nature and society’s agricultural economy. When photosystem I (PSI), a critical protein complex in photosynthesis, is photoinhibited, the photosynthetic efficiency of plants is significantly lowered for an extended period of time. PSI photoinhibition (PSI-PI) is caused by light-induced oxidative damage, which prevents PSI from transferring electrons along the photosynthetic electron transfer chain, and it occurs in conditions, which increase the electron pressure towards PSI leading to excess production of reactive oxygen species and subsequent damaging of PSI iron-sulfur clusters. This study focuses on the effects of abnormal CO2 concentration on PSI susceptibility to photoinhibition and on the combined and separate effects of abnormal CO2 and PSI-PI on gene expression of Arabidopsis thaliana. PSI-PI was induced with a specific PSI-PI-light regime, and biophysical measurements and RNA sequencing were utilized to measure the accumulation of photodamage and changes in gene expression, respectively. Unexpectedly, the severity of PSI-PI was found to be independent of CO2 concentration. Globally, both PSI-PI and abnormal CO2 induced strong and distinct responses in the gene expression of A. thaliana. Interestingly, nine genes involved in iron homeostasis were differentially expressed with PSI-PI regardless of the tested CO2 concentrations suggesting immediate release of iron from PSI, when PSI iron-sulfur clusters are damaged. A deeper investigation revealed strong up-regulation of flavonoid biosynthesis genes in the absence of CO2 indicating the need for extra protection against reactive oxygen species in these conditions. In addition, stomatal aperture size was found to be mostly independent of PSI-PI.
Keywords: CO2 concentration, FeS clusters, gene expression, photoinhibition, photosystem I, redox imbalance